Violación del principio constitucional de legalidad penal en el delito de explotación sexual derivada de trata de personas en Perú, 2021 - Vásquez Tuesta, Mayra Steffany (2022)
The human exploitation represents today one of the main concerns for the international community; faced with this context, Peru has been adapting its internal regulations in order to combat it, from which the formulation of the crime of human trafficking is derived. However, within the framework of these efforts, the legislator has also implemented a norm that violates criminal legality; and that, from our perspective, it is confusing, as is the case of the crime of "Sexual Exploitation derived from a situation of human trafficking." In this context, the main objective of this research is to establish what are the legal bases that support the violation of the constitutional principle of criminal legality in the crime of Sexual Exploitation derived from Human Trafficking in the Peruvian Penal Code. For this, we use a research method of a basic type, exploratory level and of a dogmatic legal nature. In the results it was determined that the crime of Sexual Exploitation derived from Human Trafficking reveals the violation of the requirement of certainty of the criminal law and the guarantee of strictness derived from the principle of criminal legality; due to its similarity to the crime of human trafficking for the purpose of sexual exploitation that can generate confusion and impunity in judicial practice. Finally, the need to incorporate this (Sexual Exploitation derived from Human Trafficking) as an aggravated modality of the predominant base crime (Human Trafficking) was evidenced by implying the actual objectification of the victim.